In-Operando Measurements of Volume Change of C-Si Pouch Cells. (7th July 2017) - Wen, Hao; Karulkar, Mohan; Drews, Andy
Abstract : Graphite anodes with silicon additives were coupled with NMC cathodes in pouch cells and their in-operando volume expansion during charge and discharge cycles were characterized with a high precision rig. This system continuously monitors the buoyancy force with the cells immersing in water and is shown to have a resolution of 0.01 mL. Cyclic volume change behavior clearly correlates to the voltage profiles. The impacts of cell capacity, binder, cycling rate, electrolyte and silicon weight percentage were studied. Although silicon has intrinsic volume expansion of 300% over its full range of lithiation, we found that full pouch cells with 10 wt% Si/90 wt. % graphite in anodes exhibit only ~1% volume expansion.